2018
DOI: 10.1186/s12863-018-0701-0
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of HOMER1 gene are associated with piglet splay leg syndrome and one significant SNP can affect its intronic promoter activity in vitro

Abstract: BackgroundIn our previous genome-wide association study (GWAS) on the piglet splay leg (PSL) syndrome, the homer scaffolding protein 1 (HOMER1) was detected as a candidate gene. The aim of this work was to further verify the candidate gene by sequencing the gene and find the significantly associated mutation. Then we preliminarily analyzed the effect of the significant SNP on intronic promoter activity. This research provided a reference for further investigation of the pathogenesis of PSL.ResultWe investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…Even though the specific function of HOMER1 has not been studied in pigs sufficiently, it is already known to be involved in muscle differentiation and calcium homeostasis (70), leading to myopathy in mice when expression is lost (71) and exhibited lower expression in a mouse model of Duchenne's muscular dystrophy (72). A follow up study (73) focused directly on the sequence of porcine HOMER1, defined the promoter regions and analyzed a total of 21 SNPs in the same population used in their previous analysis (17). Twelve of the SNPs were significantly associated with PCS making HOMER1 a promising candidate for PCS ( Table 2).…”
Section: Genetic Characterization Of the Splay Leg Syndromementioning
confidence: 99%
See 2 more Smart Citations
“…Even though the specific function of HOMER1 has not been studied in pigs sufficiently, it is already known to be involved in muscle differentiation and calcium homeostasis (70), leading to myopathy in mice when expression is lost (71) and exhibited lower expression in a mouse model of Duchenne's muscular dystrophy (72). A follow up study (73) focused directly on the sequence of porcine HOMER1, defined the promoter regions and analyzed a total of 21 SNPs in the same population used in their previous analysis (17). Twelve of the SNPs were significantly associated with PCS making HOMER1 a promising candidate for PCS ( Table 2).…”
Section: Genetic Characterization Of the Splay Leg Syndromementioning
confidence: 99%
“…FBXO32 was not only identified in targeted as well as in global transcriptome analyses (5, 16) but its chromosomal region harbors genetic variants (66). HOMER1 was also found to contain specific SNPs using GWAS (17) which seem to alter the expression of certain isoforms via a modified intronic promotor (73). All studies were performed in different populations indicating a general validity (Tables 1, 2).…”
Section: Current Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis showed that -700G created a transcription factor MTF-1 binding site and MTF-1 was involved in regulating NR5A2 promoter transcription activity, increasing the NR5A2 gene expression in granulosa cells of sheep. Xu et al (2018) found that polymorphisms of the HOMER1 gene are associated with piglet splay leg syndrome and the G allele of rs325197091 (A > G) may create a new binding site of transcription factor ARNT, which could enhance HOMER1 promoter activity and expression. Promoter haplotypes of the ABCB1 gene encoding the P-glycoprotein differentially affects its promoter activity by altering the transcription factor binding (Speidel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…enhancer50 or affecting promoter activity,51 according to the results of the ENCODE database. In addition, overexpressed HDAC9 may dysregulate the functions of downstream genes, and aberrant expression of HDAC9 may regulate infiltration of CD4 + T cells and Tregs to affect tumor microenvironment and therefore affect the OS of ESCC patients.…”
mentioning
confidence: 99%